Syntactic properties of male courtship song in the lesser short-tailed bat, Mystacina tuberculata - Collier, Kathleen; Parsons, Stuart (Frontiers in Ecology and Evolution, 2022)
Bats (Mammalia: Chiroptera) have sophisticated acoustic abilities adapted to many uses, including both echolocation and social vocalisations. Social vocalisations are used in a wide variety of contexts and vary greatly in acoustic arrangement and complexity. Among the most intricate are the courtship songs that males of certain species use to attract mates and advertise their qualities. To date, however, few studies have examined the phonological construction of bat songs or made a detailed assessment of the syntax used to combine different song elements. Here, we examine the syntactic construction of courtship songs in the New Zealand lesser short-tailed bat, Mystacina tuberculata, a highly vocal, lek-breeding species with exceptionally high song-output rates. We hypothesised that song construction in this species was hierarchical and non-random, but would also demonstrate a high degree of individual variation, potentially allowing for individual identification. We recorded the courtship songs of nine male bats and used manual classification of song components to examine the song structure. Here we examine whether the deployment of different song components is dependent on their position, and also determine the transition probabilities between different components. We find that the frequency of song-element production and the distribution of elements within songs are non-random at both the individual and population level, and that the number of elements used per phrase differs between individuals. Overall, we demonstrate that M. tuberculata songs are hierarchically constructed and employ phonological syntax to build syllables and phrases; we further show that bats employ high structural similarity and conservatism in the construction of syllables, while retaining a capacity for versatility and innovation that allows for considerable individual variation and, likely, individual recognition.